The Ontology of Mysticism as the Foundation of Deliberative Rationality in the Thought of Abdolkarim Soroush - Taufik Hidayatulloh; Khairil Ikhsan Siregar; Hery Purwosusanto (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2026)
The crisis of religious authority, identity polarization, and informational disruption in the contemporary public sphere indicate a tension between religious truth claims and the demands of deliberate rationality within plural societies. Abdolkarim Soroush’s thought offers a conceptual distinction between religion as a transcendent reality and religious knowledge as a historical construction, thereby opening the possibility for a reinterpretation of the relationship between mysticism and political rationality. This study aims to analyze how the ontology of mysticism in Abdolkarim Soroush’s thought establishes a normative foundation for deliberative rationality and inclusive political ethics in contemporary society. The research employs a qualitative design using normative-critical philosophical analysis. Data was collected through library research and analyzed using thematic analysis techniques. The findings indicate that Soroush’s ontology of mysticism generates an awareness of epistemic limitation that develops into epistemic humility as the basis of dialogical ethics. This awareness becomes the foundation of deliberative rationality, rejecting the absolutization of interpretation and affirming intersubjective argumentative validation. Within this construction, mysticism provides a normative orientation for inclusive political ethics that upholds interpretative pluralism and equality of arguments. It can be concluded that Soroush’s ontology of mysticism offers a philosophical basis for integrating spirituality and public rationality. Epistemic humility strengthens deliberate legitimacy in plural societies and contributes to the development of deliberative democracy grounded in metaphysical awareness and argumentative responsibility, while encouraging more inclusive, reflective, and ethically oriented public dialogue efforts.